Winding Poynting vector of light around plasmonic nanostructure. (February 2022) - Ku, Yun-Cheng; Kuo, Mao-Kuen; Liaw, Jiunn-Woei
Highlight: Surface integral equations of Fredholm equations is used to study 3D light-matter interaction. Streamline of Poynting vector winds along the long axis of a gold nanocuboid as irradiated by a circularly polarized light. Two vortexes of energy flux winding around specific corners of a gold nanocuboid are generated in the presence of a TiO2 substrate. Our simulation method provides a deeper insight into the nanoscale light-matter interaction. Abstract: A set of surface integral equations (SIEs) of Fredholm equations of the second kinds is used to study 3D light-matter interaction at the nanoscale, particularly for the plasmonic effect. Based on this method, we find that the streamline of Poynting vector (energy flux) winds along the long axis of a gold nanocuboid as irradiated by a circularly polarized light propagating in the short-axis direction; the transverse angular momentum is caused by the spin-orbit interaction of light via a plasmonic nanostructure. The spiral winding behavior of Poynting vector could be related to the helical surface currents. Moreover, we find that at an off-resonance frequency two vortexes of energy flux winding around specific corners of a gold nanocuboid are generated in the presence of a TiO2 substrate. This phenomenon may explain the cause of the selectivity of active sites for plasmon-enhanced chemical reaction. Our simulation method provides a deeper insight into the nanoscale light-matter interaction.